Empowering community and rural institutions for on-farm conservation and sustainable use of cultivated and wild tropical fruit diversity in Asia - Sthapit, B.; Lamers, H.; Reddy, M.B.C.; Idris, S.; Somsri, S.; Sutrisno Saad, N.; Ramanatha Rao, V. (2011)
On-farm (in situ) conservation of cultivated plants refers to the management of landraces/cultivars and the occasionally cultivated wild relatives (as in the case of fruit species like mango) in the very place where they developed their present-day characteristics. Fruit tree varieties and related good practices innovated by farmers in their home-gardens and semi-commercial orchards are an important source of genetic resources that are still underutilized and neglected considering their potentially lucrative market value. This poster describes a participatory and innovative method/tool for assessing the fruit genetic diversity in farming communities in order to develop livelihood options based on diversity available to farmers as well as conservation actions.